Decision analysis in project management: An overview - Booker, Jane M.; Bryson, Maurice C. (IEEE transactions on engineering management, 1985)
Decision theory encompasses or interacts with many different subject-matter fields. For the manager who requires some access to the literature in these diverse areas, this paper provides a broad overview of the subjects and a guide to further reading in decision theory, emphasizing its application to R&D project management. This paper includes very general topical summaries in utility theory, mathematical programming, statistical methods, scoring and ranking methods, and cognitive science together with a list of 96 references. A more complete reference list organized by topic and individually annotated, is available from the authors.